Seleção de habitat para nidificação por aves em uma área preservada da Mata Atlântica do sudeste do Brasil - Perrella, Daniel Fernandes (Universidade Federal de São Carlos, 2019)
Birds naturally present a number of ecological requirements to survive in complex habitat environments where they live and the ability to select suitable and safe nesting sites has been shown to be a particularly important adaptive factor in the life cycle of these animals. In Neotropical forests, naturalists have long suggested that even non-aquatic birds often do reproduce near water bodies, which however, is still poorly addressed. From 2016 to 2018, nests of understory birds were studied at Carlos Botelho State Park, São Miguel Arcanjo, SP, and the influences of forest streams for nest site selection and nest survival were investigated, which is presented here in three chapters. In the first chapter, nests were searched near forest-streams and far from any watercourse in an attempt to compare nest density between these two situations. In the second and third chapters, nests of Chiroxiphia caudata, Rhopias gularis and Onychorhynchus swainsoni, which nested near or above forest streams, were monitored and we tested if these species could select specific stretches of the streams to build their nests, and we tested if stream characteristics, i.e. stream width, water depth, and water speed could interfere with their reproductive success. Further, in the third chapter, other reproductive parameters of O. swainsoni, which is endangered, were observed, such as nest and eggs measurements, incubation and nestling periods, breeding phenology, nesting success, and density of reproductive pairs along streams. We found 63 nests of 18 species along streams and only one far from them. We revealed that nest density was much higher near forest streams (5.3 nests/ha), than far from water (0.1 nests/ha). We showed that none of the stream covariates explained nest site selection for the three studied species, although water depth and distance to water were correlated to nest survival for R. gularis. In the third chapter we showed that O. swainsoni selected only the largest forest streams to establish their reproductive territories, and that their reproductive rates and breeding territory densities were low compared to other forest understory passerines, which is likely involved in its rarity. This study comprises the first carried out in the Neotropical region to provide information on nest density in a well-preserved Atlantic Forest remnant, and the streams that permeate this forest seem to provide important reproductive habitats for several bird species, although the mechanisms involved in nest site selection varied among the different species.
Keywords: Ninhos; Riachos; Sub-bosque; Sucesso reprodutivo; Variáveis ambientais; Breeding success; Environmental variables; Nests; Rainforest; Streams; Forest understory; CIENCIAS BIOLOGICAS::ECOLOGIA